A behavior of reinforced vibrocompacted stone column in peat - Prasad, Arun; Kazemian, Sina; Kalantari, Behzad; Kim Huat, Bujang (Universiti Putra Malaysia Press, 2012)
In the literature, several methods of ground improvement have been presented including compacted stone columns. The bearing capacity of the granular column is governed mainly by the lateral confining pressure mobilized in the soft soil to restrain or prevent bulging of the granular column. Therefore, the technique becomes unfeasible in peat that does not provide sufficient lateral confinement. This condition can be overcome by encasing the stone column with geogrid. This paper investigates the performance of the geogrid encased vibrocompacted stone column in peat. This study was carried out using PLAXIS software equipped with unit cell concept. The peat was modelled using soft soil model and the stone column using Mohr-Coulomb soil model, respectively. The geogrid was modelled using the geogrid option and could take only tensile force. The results indicate that the geogrid encased stone column can take much higher load in comparison to ordinary stone columns as the stiffness of the column increases. Meanwhile, the length of encasement also varied and it was observed that it was very effective up to about two times the diameter of the column. It also increased the column stiffness, and therefore led to a significant strain reduction. It was also observed that the columns at a spacing of three times the diameter are very effective. The results presented here can be used by the geotechnical engineers to design the geogrid reinforced stone column based on the strength of the soil, diameter of the column, spacing of the columns and stiffness of the geogrid.